2012
DOI: 10.1080/17523281.2012.711767
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of cognitive impairment in a rural in-patient substance misuse treatment programme

Abstract: Cognitive impairment is one factor known to affect people's ability to participate in substance misuse treatment because of the range of cognitive, behavioural and emotional problems such impairment can cause. Some of the behaviours described as common features of cognitive impairment, such as impaired selfmonitoring and self-regulation and lack of initiative are seen in some treatment modalities to be causes and consequences of addiction thereby prescribing a moral rationale to behaviour that may have a physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Lives Lived Well’s research program has used both state-wide and local treatment episode data to highlight the need for treatment services to address homelessness in treatment planning [12]; identify the prevalence of people in treatment who have a cognitive impairment [14] and investigate access of Aboriginal women to drug and alcohol treatment [15]. To appropriately shape service delivery an analysis of amphetamine treatment episodes was required.…”
Section: Study Contextmentioning
confidence: 99%
“…Lives Lived Well’s research program has used both state-wide and local treatment episode data to highlight the need for treatment services to address homelessness in treatment planning [12]; identify the prevalence of people in treatment who have a cognitive impairment [14] and investigate access of Aboriginal women to drug and alcohol treatment [15]. To appropriately shape service delivery an analysis of amphetamine treatment episodes was required.…”
Section: Study Contextmentioning
confidence: 99%
“…For example, it has been suggested that cognitive dysfunctioning often associated with MBID (e.g. attentional dysfunctioning, impaired organisational and planning skills and impaired self-monitoring) hamper the usefulness of treatment programmes based on cognitive and behavioural change (Allan et al 2012). Identifying such factors in an early phase of the treatment thus guides practitioners in their choices for treatment interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In their prevalence study, Allan et al (2012) defined cognitive impairment as an umbrella term used to refer to the impacts of long-term drug or alcohol use, acquired or traumatic brain injury, intellectual disability, or Foetal Alcohol Spectrum Disorder (FASD) [21]. While each of these conditions can vary in severity and impact, they have similar broad effects on executive function [18, 22].…”
Section: Introductionmentioning
confidence: 99%
“…While each of these conditions can vary in severity and impact, they have similar broad effects on executive function [18, 22]. Individuals with some form of cognitive impairment will typically experience one or more of the following: impaired ability to plan and make decisions, reduced ability to evaluate consequences, a preference for reward-seeking goals, impulsivity and attentional dysfunction, lack of initiative, memory deficits, impaired self-monitoring and self-regulation, and an inability to benefit from experience [18, 21]. Further, those with some form of cognitive impairment are more likely to experience poor concentration, depression, emotional instability, irritability, impulsive or inappropriate behaviour, reduced ability to problem-solve and inflexible thinking [23, 24].…”
Section: Introductionmentioning
confidence: 99%